The Impact of Soy Fortification in Early Childhood Foods on Child Nutrition Outcomes: A Systematic Review - AGUMBA, Susan Akinyi; SEREM, Charlotte; WAMUNGA, Florence; WERE, Gertrude (African Journal of Nutrition and Dietetics, 2026)
Child malnutrition remains a significant public health challenge that disproportionately affects children in low- and middle-income countries (LMICs). The problem is further intensified by widespread food insecurity and limited access to affordable animal-source protein in many of these settings. Soy-fortified complementary foods have therefore emerged as a promising nutritional intervention due to their high nutritional value, local availability, affordability, and general acceptability among communities. This review examined the impact of soy fortification in early childhood foods on child nutrition outcomes. The review followed the PRISMA 2020 guidelines and involved a comprehensive search of peer-reviewed studies published between 2012 and 2025 across several databases, including the Cochrane Library, Google Scholar, PubMed, Embase, and PLOS One. Fourteen eligible studies conducted in LMICs were included, comprising randomized controlled trials, test-feeding experiments, non-inferiority trials, and experimental formulation and sensory evaluation studies. Most of the reviewed interventions demonstrated significant improvements in key anthropometric indicators such as weight-for-age, height-for-age, weight-for-height, and mid-upper arm circumference, as well as reductions in the prevalence of wasting and underweight. Soy-based formulations were also associated with improved recovery rates among children with severe and moderate acute malnutrition and increased serum concentrations of essential micronutrients such as zinc and iron. In addition, soy-fortified products generally showed higher acceptability and improved nutritional quality compared to traditional complementary foods. However, the effectiveness of these products depended largely on formulation quality and the bioavailability of nutrients. Despite some variability in findings across studies, the overall evidence strongly supports the integration of soy-fortified foods into community-based nutrition programs aimed at addressing child undernutrition. These findings provide valuable guidance for policymakers and healthcare providers by highlighting soy-based formulations as an evidence-based intervention to improve child growth, nutrition, and survival.